Two Sample Sputum Microscopy and Revised Tuberculosis Case Definition by WHO: Bangladesh Perspective - Dewan, Gourab (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Three samples of sputum (Spot-Morning-Spot) used for screening patients with suspected pulmonary tuberculosis in Bangladesh. At least two positive samples required for case definition. Cases with single positive smear require additional chest x-ray or culture. The study was done to evaluate utility of two sputum samples for case detection and whether adoption of new case definition (requiring single positive sample) recommended by World Health Organization adds advantage over current case definition for diagnosing smear positive pulmonary tuberculosis. MATERIAL AND METHODS: Retrospective analysis of sputum positive pulmonary tuberculosis cases taken from two separate hospitals in southeast Bangladesh. Frequency, pattern and increment of smear positivity noted in each samples. Smear positive cases reevaluated using proposed case definition and compared with current national definition. RESULTS: Sputum positivity for first, second and third samples was 71.6%, 99.0% and 97.3% respectively (n=408). Incremental new case detection rate was 71.6%. 28.1% and 0.2% in same order. Morning sputum had the highest sensitivity for case detection (99.0%). Incremental new case detection from third sample was negligible and using current case definition of sputum positive tuberculosis in three samples left some inconclusive cases requiring further x- ray or culture for diagnosis pending decision further. Adoption of new case definition reduces number of inconclusive cases and diagnostic delay. CONCLUSION: Two sputum samples adequate for screening of tuberculosis suspects. Adopting new case definition will reduce number of cases left inconclusive with microscopy alone (using current case definition). This will strengthen role of microscopy in tuberculosis detection in low resource setting. DOI: http://dx.doi.org/10.3126/jucms.v2i4.12034 Journal of Universal College of Medical Sciences (2014) Vol.02 No.04 Issue 08 Page: 1-6